Perspectives and State of the Art of Membrane Separation Technology as a Key Element in the Development of Hydrogen Economy - M. Olga Guerrero-Pérez (Membranes)
Due to the objectives established by the European Union and other countries, hydrogen production will be a key technology in the coming decades. There are several starting materials and procedures for its production. All methods have advantages and disadvantages, and the improvements in their performance and decreases in operational costs will be decisive in determining which of them is implemented. For all cases, including for the storage and transport of hydrogen, membranes determine the performance of the process, as well as the operational costs. The present contribution summarizes the most recent membrane technologies for the main methods of hydrogen production, including the challenges to overcome in each case.